Reviews of recent publications (Studies in 20th & 21st Century Literature, 2009)
Sara Lennox. Cemetery of the Murdered Daughters: Feminism, History, and Ingeborg Bachmann by Kristin T. Vander Lugt Birgit Tautz. Reading and Seeing Ethnic Differences in the Enlightenment: From China to Africa by Susanne Kelley Patrick Greaney. Untimely Beggar. Poverty and Power from Baudelaire to Benjamin by Christine Rinne Philip Payne, Graham Bartram, and Galin Tihanov, eds. A Companion to the Works of Robert Musil by Geoffrey C. Howes Jennifer Willging. Telling Anxiety: Anxious Narration in the Work of Marguerite Duras, Annie Ernaux, Nathalie Sarraute and Anne Hébert by Natalie Edwards Michael Lucey. Never Say I: Sexuality and the First Person in Colette, Gide, and Proust by Elissa Gelfand Anthony Waine. Changing Cultural Tastes. Writers and the Popular in Modern Germany by Katrin Völkner Susan Ireland and Patrice Proulx, eds. Textualizing the Immigrant Experience in Contemporary Quebec by Amy Hubbell Cristina Peri Rossi. State of Exile. Trans. Marilyn Buck. by Reina Ruiz
Keywords: Sara Lennox; Cemetery of the Murdered Daughters: Feminism History and Ingeborg Bachmann; Kristin T. Vander Lugt; Birgit Tautz; Reading and Seeing Ethnic Differences in the Enlightenment: From China to Africa; Susanne Kelley; Patrick Greaney; Untimely Beggar Poverty and Power from Baudelaire to Benjamin; Christine Rinne; Philip Payne; Graham Bartram; Galin Tihanov; A Companion to the Works of Robert Musil; Geoffrey C. Howes; Jennifer Willging; Telling Anxiety: Anxious Narration in the Work of Marguerite Duras Annie Ernaux Nathalie Sarraute and Anne Hébert; Natalie Edwards; Michael Lucey; Never Say I: Sexuality and the First Person in Colette Gide and Proust; Elissa Gelfand; Anthony Waine; Changing Cultural Tastes Writers and the Popular in Modern Germany; Katrin Völkner; Susan Ireland; Patrice Proulx; Textualizing the Immigrant Experience in Contemporary Quebec; Amy Hubbell; Cristina Peri Rossi; State of Exile; Marilyn Buck; Reina Ruiz